The Role Of Local Medications In Treating Purulent Wounds On The Lower Extremities (Texas Journal of Medical Science, 2024)
Study of the effect of the new drug Reomannisol on endogenous intoxication and wound healing, taking morphological aspects into the complex treatment of experimental diabetic foot syndrome